A performance analysis of tidal turbine conversion system based on control strategies. (February 2019) - Omkar, K.; Karthikeyan, K.B.; Srimathi, R.; Venkatesan, Nithya; Avital, E.J.; Samad, A.; Rhee, S.H.
Abstract: Energy efficient generation from renewable energy sources is of major concern nowadays. A horizontal axis marine current turbine (HAMCT) of diameter 1.9 m is modelled using the blade element momentum (BEM) scheme and the turbine output parameters are given as an input to the electrical system for a tip speed ratio (TSR) of 5 and a power coefficient of 0.4. The design aspects of a buck-boost converter with proportional integral (PI) and sliding mode controller (SMC) is investigated for HAMCT system, with the highest power output of about 15.6 kW for a water velocity of 3 m/s. A comparison between PI controller and SMC are analyzed for the tidal turbine conversion system to obtain the desired output voltage with high efficiency is discussed here. The dynamic variation on load side to be controlled with dual loop controller to regulate the output voltage and to optimize the input current. In this paper performance and resemblance of control techniques which include sliding mode controller and PI controller are analysed with step and bode plot response. The system is designed for an output voltage range of 0.38 kV to 2.4 kV which is suitable for DC microgrids. The performance of HAMCT coupled with PMSG and the power converter with a controller is modelled and designed under MATLAB/SIMULINK environment.